2010
DOI: 10.1093/toxsci/kfq117
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Adduct on Tyrosine 411 of Albumin in Humans Poisoned by Dichlorvos

Abstract: Studies in mice and guinea pigs have shown that albumin is a new biomarker of organophosphorus toxicant (OP) and nerve agent exposure. Our goal was to determine whether OP-labeled albumin could be detected in the blood of humans exposed to OP. Blood from four OP-exposed patients was prepared for mass spectrometry analysis by digesting 0.010 ml of serum with pepsin and purifying the labeled albumin peptide by offline high performance liquid chromatography. Dimethoxyphosphate-labeled tyrosine 411 was identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…Other approaches for detecting OPNA exposure include the measurement of OPNA hydrolysis products in urine [12], OPNA fluoride reactivation in blood [11] and OPNA adduction to albumin in blood [18]. OPNA metabolites including GB, soman, cyclosarin, VX and Russian-VX phosphonic acids are rapidly detected in urine using liquid chromatography tandem mass spectrometry (LC-MS/MS) [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches for detecting OPNA exposure include the measurement of OPNA hydrolysis products in urine [12], OPNA fluoride reactivation in blood [11] and OPNA adduction to albumin in blood [18]. OPNA metabolites including GB, soman, cyclosarin, VX and Russian-VX phosphonic acids are rapidly detected in urine using liquid chromatography tandem mass spectrometry (LC-MS/MS) [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, albumin was studied; peptide fragments of human serum albumin were analyzed in response to chlorpyrifos oxon, dichlorvos, diisopropylfluorophosphate, and sarin. [50][51][52][53] Complexes of Ni, Co, and Fe, were evaluated for the OPs sensing, but Cu 2+ gave the best response indicating that the ligand had to accommodate enough vacancy. Thus, at this early point it was concluded that "copper complexes may adsorb and desorb phosphorus esters in air."…”
Section: Mass Spectrometricmentioning
confidence: 99%
“…Similarly, Noort et al (2009) suggested that the affinity of OP for albumin could provide a mechanism for a more complete assessment of OP pesticide exposure. In addition, a mass spectrometry method to identify exposure to several pesticides (dichlorvos, chlorpyrifos oxon and aldicarb) based on the identification of pesticide adducts on the active site (i.e., serine) of human BChE has been proposed by Li et al (2010a).…”
Section: Esterase Inhibition As a Biomarker Of Pesticide Exposure In mentioning
confidence: 99%
“…Measurements are performed on blood, urine or homogenates of tissues that are obtained from biopsies. Specifically, adducts have been detected on tyrosine 411 of human albumin exposed to dichlorvos (Li et al, 2010a), and adducts have also been identified at Ser 198 of human BChE upon exposure to carbofuran (Li et al, 2009) and on the DNA-adduct 8-hydroxy-2-deoxyguanosine (8-OHdG) in the plasma of farm workers (Tope & Panemangalore, 2007), among others. Pesticides have been considered as potential mutagens because they contain ingredients capable of causing changes in DNA.…”
Section: Wwwintechopencommentioning
confidence: 99%